Assessment of Stroke Case-fatality, Disability, Perceived Needs and Barriers for Care among First-ever Stroke Patients Attending a Tertiary Care Neuro-specialty Center in India: A Cross-sectional Study - Azad Devyani; Pradeep S. Banandur; Gautham Melur Sukumar; Girish Baburao Kulkarni; S. Mythirayee; Himani Rathore (Indian Journal of Community Medicine)
Background: Stroke is a major public health and clinical challenge that results in significant mortality and disability. Stroke survivors require care and support, particularly during the crucial 3 months post-stroke when 95% of functional neurological recovery occurs. To estimate case-fatality and extent of disability, assess perceived needs, barriers, and unmet needs for care, and ascertain pathways to care post-discharge (at 3 months) among first-ever stroke patients attending a tertiary care neuro-specialty center in India. Material and Methods: A cross-sectional descriptive study was conducted among patients receiving care within [NIMHANS]. Patients with confirmed computed tomography (CT) scans experiencing their first-ever stroke between September 1 and October 31, 2022, were contacted between November 1, 2022, and March 31, 2023. A pre-tested semi-structured questionnaire was used to collect information. Descriptive statistics were performed using STATA version 16. Results: Stroke fatality among study subjects was 13.8%. Almost half (49.09%) had some form of disability, with 40% having moderate to severe disability. The majority perceived the need for follow-up visits (87%) and compliance with stroke medication (84%). Distance and transportation (60%) were cited as the main barriers to care. After discharge, the majority preferred healthcare facilities close to their homes (60%). Conclusions: This study emphasizes the need for stroke survivors to have follow-up and compliance with medication, along with various unmet needs such as de-addiction services, vocational training, and emotional support. A network-based multi-disciplinary approach, along with a comprehensive hub and spoke model of stroke management services, could help address these challenges and improve patient outcomes.